Biochemical Analysis and Coagulation Profiling of Canine Fresh Frozen Plasma - Pai, Namrata; Baranidharan, Rengaswamy; Chandrasekar, Muniswamy; Kavitha, Santhanakumar (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
In India, canine plasma transfusion therapy in veterinary clinical practice has risen exponentially over the past few decades. Several indications for the use of canine fresh frozen plasma (FFP) have been considered, including coagulopathies associated with liver disease, rodenticide poisoning, hypoalbuminemia, acute pancreatitis and as a resuscitative fluid in septic shock. Healthy canine blood donors were subjected to jugular phlebotomy for whole blood collection. Canine FFP was prepared as per standard centrifugation protocols in the TANUVAS Animal Blood Bank (TABB), Madras Veterinary College Teaching Hospital and stored aliquots of samples were subjected to in vitro analysis. The findings indicated that canine FFP is hyperglycemic (384±10.54 mg/dL), hypernatremic (158.1±2.61 mEq/L), with normal protein (5.32±0.11 g/dL) and lower albumin (2.25±0.03 g/dL). Moreover, FFP was found to retain hemostatic activity, ascertained by normal prothrombin time (PT) (7.04±0.7 sec) and activated partial thromboplastin time (APTT) (22.01±0.89 sec), and normal fibrinogen (4.5±0.26 g/dL). These observations may serve as reference of the canine fresh frozen plasma constituents.
Keywords: Canine; Coagulation; Electrolytes; Fresh Frozen Plasma